Synthesis of ZrO2:Dy3+ Nanoparticles: Photoluminescent, Photocatalytic, and Electrochemical Sensor Studies. (16th August 2022) - Gurushantha, K.; Anantharaju, K. S.; Kottam, Nagaraju; Keshavamurthy, K.; Ravikumar, C. R.; Surendra, B. S.; Murugan, A.; Murthy, H. C. Ananda
Abstract : Solution combustion was employed to create a series of ZrO2 :Dy 3+ (1-11 mol percent) nanoparticles (NPs) using oxalyl dihydrazide (ODH) as the fuel. ZrO2 :Dy 3+ NPs were subjected to calcination at about 700°C. ZrO2 :Dy 3+ NPs comprised of 1 to 11 mol% of Dy 3+ were characterized by employing the X-ray diffraction (XRD), transmission electron microscopic (TEM), UV-visible, and X-ray photoelectron spectroscopic (XPS) techniques. The crystallite diameters of 1 to 11 mol% ZrO2 :Dy 3+ NPs were observed to range from 8.1 nm to 16.3 nm, exhibiting spherical shape. According to BET tests, the pore volume of ZrO2 :Dy 3+ NPs was determined to be 100.129 cm 3 /g. The mean pore diameter of ZrO2 :Dy 3+ NPs was determined to be 4.803 nm from the Barrett-Joyner-Halenda (BJH) plot. The photoluminescence and photocatalytic dye degradation properties of ZrO2 :Dy 3+ NPs were investigated. The acid red 88 (AR88) dye was applied to appraise the photocatalytic activities of the NPs under UV irradiation. ZrO2 :Dy 3+ NPs with 3 mol% Dy 3+ exhibited improvised photocatalytic activity due to the operative departure of charge carriers. The electrochemical examination of ZrO2 :Dy 3+ NP modified carbon paste electrode in 0.1 N HCl demonstrated considerable redox potential output, as evidenced by cyclic voltammetric and amperometric measurements. The electrochemical sensor studies on ZrO2 :Dy 3+ NPs exhibited potentiality towards sensing of highly toxic metals like mercury and lead.